Challenges and Solutions Perceived by Educators in an Early Childcare Program for Refugee Children - Busch, Julian; Bihler, Lilly-Marlen; Lembcke, Hanna; Buchmüller, Thimo; Diers, Katerina; Leyendecker, Birgit (Frontiers in Psychology, 2018)
Immigration to Germany peaked in 2016. More than 105,000 refugees below the age of seven years arrived within twelve months. Since then, Germany and other host nations have been in need of strategies to cover the emerging demand for childcare services. The German federal state North-Rhine Westphalia has funded a specialized early childhood and care (ECEC) program for recently arrived refugees. The present study investigated challenges and possible solutions in this specialized ECEC. In a pilot study, inductive content analysis of n1 = 28 semi-structured interviews with early childhood educators revealed 19 distinct challenges and four generic categories for solutions (provide clear and predictable structures, involve and support parents, ensure adequate structural features of the childcare group, convey trust and feelings of competence). For the main study, identified challenges were transcribed into items for a closed-format questionnaire, which was distributed to a second sample of educators (n2 = 96). Challenges perceived as most difficult concerned language barriers and communication with parents. An exploratory factor analysis of the challenges questionnaire yielded four underlying domains (interpersonal stress, feasibility and attendance, cultural and communication barriers, structural features of a childcare group). Our study provides a first basis to adapt childcare settings for refugees, and to guide staff training for this special group. We discuss evidence in regard to understanding how ECEC programs can successfully promote refugee children’s psychosocial adaptation and educational outcomes.